Exploration of Structural and Physical Characteristics of a Ceramic-Based System via Flame Thermal Spraying - Farah S. Khasrw; Aya N. Abdullah; Salih Y. Darweesh (Eximia, 2024)
Flame thermal spraying is an important technique in surface treatment of many materials exposed to external corrosion, including turbine blades in power plants, bridges, and oil pipelines. Therefore, a ceramic material represented by aluminum oxide Al2O3 was used as a base material and copper metal Cu was added at different reinforcement ratios of 5%, 10%, 15%, 20%, 25%Wt. To form a cermet alloy. The two powders were mixed after taking into account the copper concentrations, and the mixture was placed in the flame thermal spraying device crucible. The acetylene gas ratio was fixed at 0.7 bar and oxygen at 4 bar as the best mixing ratios obtained. The coating process was carried out on out-of-service turbine blade bases with dimensions of 20mm×5mm in a circular shape. After completing the coating process, the samples were sintered in a thermal oven at 1100°C for only one and a half hours. The scanning electron microscope (SEM) of the samples was examined and it was found that by adding copper we get a regular and homogeneous structure, and it was found that the best reinforcement with metal is 25%Wt. After sintering, it was also found that the average grain size is approximately 109nm. An EDX spectroscopy was also conducted to show the materials that were mixed for both alumina and copper. Some mechanical properties were also examined which showed that the best mixing ratio is (75%Wt.Al2O3-25%Wt.Cu) after sintering, at which the micro-Vickers hardness was found to be (605 kg/mm2), and the wear rate was calculated which gave the lowest value (1.84×10-6g/cm). While the adhesive strength was calculated for a coated and uncoated sample to find that the best mechanical adhesive strength is (53 MPa). The true porosity and water absorption were calculated to give the lowest values at the lowest reinforcement ratio which is 25%Wt.